Rancang Bangun Aplikasi Penetapan Dosis Obat Individual Menggunakan Pemrograman Visual Basic.Net Berdasarkan Perhitungan Data Farmakokinetika - Usman, Ari; Zebua, Nilsya Febrika (Sinkron : jurnal dan penelitian teknik informatika, 2017)
The drug is a substance that when inserted into the human body in the right measure will cure the disease but when the measure exceeded it will happen poisoning. The dose of a drug that is indicated in Pharmacopoeia Indonesia consists of maximum dose is prevalent and just based on age (adult or children) without regard to the patient's kidney condition. The condition of patients with impaired kidneys cannot receive doses of common good, necessary adjustments to the dose pharmacokinetics based on calculations with numbers of serum creatinine. Drugs with a narrow therapeutic range and nephrotoxic can aggravate the condition of kidney patients. Therefore, this research aims to build a visual basic.net application of individual dose calculations based on the pharmacokinetics formula. Visual Basic.net programming language is one that can be implemented into the computer in either a State of its own (standing alone) or network (network).